Climate change is likely to affect the distribution but not parapatry of the Brazilian marmoset monkeys (Callithrix spp.). Issue 4 (11th December 2018) - Braz, Alan Gerhardt; Lorini, Maria Lucia; Vale, Mariana Moncassim
Abstract: Aim: Parapatric distributional patterns can arise from abiotic or biotic factors, or from dispersal barriers. Climate change can potentially affect parapatry by changing species' potential geographic distribution, and thereby widening or shrinking contact zones. Here, we study the effects of climate change on all six species in the genus Callithrix, a group of small‐sized Neotropical primates that is distributed parapatrically in eastern Brazil, allegedly due to biotic interactions. Location: Atlantic Forest, savanna and xeric shrublands from Brazil. Methods: We explore a method to investigate potential effects of climate change on the distribution of parapatric species by (a) determining whether the parapatric pattern is explained by abiotic (climate) or biotic (species' interactions) factors using niche equivalency and niche similarity tests; (b) estimating each species' potential distribution under current and future climatic conditions, using ecological niche models; and (c) performing a pixel‐by‐pixel analysis in order to constrain distribution overlap between species pairs in which parapatry is maintained by biotic factors. Results: We found that parapatry in Callithrix is maintained mostly by abiotic factors, except for two species pairs ( Callithrix aurita vs. C. flaviceps and C. geoffroyi vs. C. penicillata ) in which biotic factors are more likely to be acting. Our proposed method is able to produce better models than conventional ecological niche modelling, predicting net reductions in distribution area for some species and increases for others; however, reductions generally exceeded expansions. The reduction in potential distribution areas would maintain Callithrix flaviceps as Endangered under IUCN criteria. Main conclusions: Despite range contractions and the loss of area of sympatry, climate change is unlikely to affect the parapatric distribution patterns in Callithrix, nor intensify interspecific interactions.